Impact of tumor size on the difficulty of minimally invasive liver resection. Issue 1 (January 2022) - Kabir, Tousif; Syn, Nicholas; Koh, Ye-Xin; Teo, Jin-Yao; Chung, Alexander Y.; Chan, Chung-Yip; Goh, Brian K.P.
Abstract: Introduction: We performed this study in order to investigate the impact of tumour size on the difficulty of MILR, as well as to elucidate the optimal tumour size cut-off/s to distinguish between 'easy' and 'difficult' MILRs. Materials and methods: This is retrospective review of 603 consecutive patients who underwent MILR between 2006 and 2019 of which 461 met the study inclusion criteria. We first conducted an exploratory analysis to visualize the associations between tumor size and various surrogates of laparoscopic difficulty in order to determine to optimal tumor size cutoff for stratification. Visual inspection of flexible spline-based models as well as quantitative evidence determined that perioperative outcomes differed between patients with tumor size of 30–69 mm and tumours ≥70 mm. These cutoffs were used for further downstream analyses. Results: The cohort of 461 patients was divided into 3 groups based on tumour diameter size. Patients with larger tumours experienced longer operating times ((PGroup 2 vs 1 <0.001, PGroup 3 vs 1 <0.001, PGroup 3 vs 2 <0.001), higher blood loss (PGroup 2 vs 1 <0.001, PGroup 3 vs 1 <0.001, PGroup 3 vs 2 <0.001), as well as significantly longer hospital stay (PGroup 2 vs 1 <0.001, PGroup 3 vs 1 <0.001, PGroup 3 vs 2 <0.001). There was a monotonic trend towards increasing blood transfusion rates (P = 0.006), overall morbidity (P = 0.029) and 90-day mortality rates (P = 0.047) with increasing tumour size. Conclusion: Although tumour size of 30 mm serves as an optimal cut-off for predicting difficult resections as per the Iwate criteria, a trichotomy (<30 mm, 30–69 mm, ≥70 mm) may provide additional granularity. Further large-scale prospective studies are needed to corroborate these findings.